Penerapan Prinsip Desain Le-Corbusier Pada Pondok Pesantren Modern Di Kota Dumai - Muhammad Iqbal Irzaiin; Gun Faisal; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Entering the Era of globalization with marked advances in education made many traditional Islamic Boarding began to gradually enter the general education curriculum in it, changes thatoccur in the actual Boarding School is the anticipation of Pondok pesantren itself in answering the challenges of globalization. According to data from the Dept. of Education Dumai City (2018),each new school year about 1500 students from Dumai wish to continue education at boarding school, 1500 only 300 were in school in Dumai, the rest go to school abroad, students male moredominate in the quarters. The problems that exist in the Boarding School in Kota Dumai is, the limited capacity of the prospective students due to insufficient number of classrooms, the competitiveness amongst prospective students with prospective students the local area entrants, the boarding students are limited, lack of facilities offered by the Boarding School to prospective students to make prospective students looking take boarding school facilities. limitations for landand the high price of land the days to come will have an impact on the shape and composition of school buildings, especially the shape of the building Boarding School, in anticipation of the highprice of land in the future, the planning and design of Modern Boarding with this form of the mass of a single building, To support the mass of a single building design, architects experienced in thisfield are Le Corbusier, almost all of his work resulted in a single building mass.`Keywords: Le-Corbusier, Islamic Boarding School, Single Building mass.